Acute limb ischemia in an adolescent with COVID-19 and systemic scleroderma: a case report - Mark Jason D. C. Milan; Leonila F. Dans; Vanessa Maria F. Torres-Ticzon (BMC, 2022)
Abstract Background Juvenile Scleroderma is a rare autoimmune disease of the connective tissue. Its concurrence with COVID-19 can lead to limb ischemia as both disease entities are pro-inflammatory and pro-thrombotic. To date, there is no case report describing the symptomatology and course of disease in patients with juvenile Scleroderma and COVID-19. Case presentation An adolescent with acute limb ischemia presented with a history of generalized hypo-and-hyperpigmented skin lesions and mild, non-productive cough. She tested positive for SARS-CoV-2 on nasopharyngeal swab RT-PCR. Further work-up revealed elevated anti-phospholipid antibodies, anti-nuclear antibody, and D-dimer; low Protein S activity; and evidence of peripheral arterial disease on imaging studies. She was started on peripheral vasodilators, Methotrexate, and anticoagulation. Close monitoring of the affected limbs and other organs involved was done. Control of limb ischemia was achieved after 4 months of regular Cyclophosphamide infusion. Continued multi-disciplinary care was ensured for this patient. Conclusion There is evolving knowledge about the interplay of COVID-19 hyperinflammatory state and rheumatologic disorders. COVID-19 is thought to exacerbate cutaneous manifestations of autoimmune disorders via antigen protein mimicry and cytokine imbalance. Moreover, COVID-19 is characterized by complex hematopathologic processes that put a patient in a hypercoagulable state. Elevated D-dimer can be seen in both COVID-19 and systemic sclerosis owing to their pro-thrombotic sequela. There is scarcity of data on the association of Protein S activity with COVID-19 and systemic sclerosis. More studies need to be carried out to ultimately arrive at a consensus on thrombosis prophylaxis for patients with Scleroderma and COVID-19.